Influence of sodium diffusion from substrates on performance of SnS/CdS thin-film solar cells. Issue 42 (14th October 2019) - Cho, Jae Yu; Shin, Kyeongrok; Lee, Hyo Seok; Neerugatti, KrishnaRao Eswar; Heo, Jaeyeong
Abstract : The influence of Na diffused from substrates on SnS/CdS thin-film solar cells was investigated. Abstract : The influence of Na doping in vapour-transport-deposited SnS thin-film solar cells (TFSCs) was investigated based on the choice of substrate, such as soda-lime glass (SLG) and Eagle XG glass, without an external supply of Na. Our results show that the quantity of Na not only impacts the growth orientation of SnS, but also varies the efficiencies from 2.66% to 2.93% for SLG- and Eagle XG-based SnS TFSCs, respectively.